Effects of FluidGro on Centennial Supply: implementing effective marketing strategies to enhance sales and profitability - Laws, Brandon B. (Kansas State University, 2012)
Because agriculture is a cornerstone in the U.S. and World economies, the agricultural retail industry is becoming more competitive. To gain a competitive advantage, agricultural retailers must take advantage of competencies that they have. The thesis provides an in depth analysis of how FluidGro products effect the profitability of Centennial. It explores the issues impacting Ag Retail and how marketing concepts and theories can make a retailer achieve success in volatile times. Insight is provided regarding how Centennial Ag Supply can use those strategies to give them a low cost position and a differentiated product and how Centennial can improve profitability by implementing effective marketing strategies for the FluidGro brand of products. Finally, a couple of capital improvement options that Centennial Ag can invest in to increase the sales and profitability of their FluidGro product line and what impact that will have on company sales and profitability. A net present value analysis is used to analyze the capital improvements and linear regressions estimate the profitability of the FluidGro product line and how this will contribute to increased profitability to the parent company, Centennial Ag Supply. Results indicate that Centennial should first invest in a wholesale division. Next, Centennial should invest in a heat exchanger to allow it to manufacture additional products.
Keywords: Marketing strategy; Agriculture retailer; Boutique fertilizer products; FluidGro; Wholesale Division; Agriculture, General (0473); Business (0310); Economics, Agricultural (0503)